Efektivitas Penggunaan Musik terhadap Konsentrasi Belajar Biologi Kelas X SMA Pembangunan Laboratorium UNP Kota Padang - Befahandher, Ayka; Magistarina, Elrisfa (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the effectiveness of music in improving the learning concentration of class X students of SMA Pembangunan Laboratorium UNP Kota Padang, divided into an experimental group of 6 students and a control group of 6 students. The method used in this experiment is a pretest-posttest control group design. The experimental group studied with music, while the control group did not. Data collection techniques were carried out through learning concentration tests before and after treatment, which can be in the form of the results of completing Biology practice questions, direct observation of students during the learning process, and testing student concentration using psychological apparatus. The data obtained were analyzed using statistical methods to compare differences in learning concentration between groups, such as t-tests or analysis of variance (ANOVA). The results of the study showed a significant increase in learning concentration in the experimental group compared to the control group. Statistical tests supported this finding, showing that the average difference in learning concentration scores before and after treatment was higher in the experimental group. The use of music can improve students' learning concentration in Biology subjects. Teachers can use music to create a more conducive learning environment. These findings can be applied in more effective teaching methods in the classroom.